Investigating Thai Freshmen Students' Understanding in Five Basic Essential Properties of Laser Beam - Jintawat Tanamatayarat (2018)
Lasers play an important role in everyday life due to special properties of their emitted light. Students are familiar with lasers not only from lectures or textbooks, but also in real life. The evaluation of students' knowledge in basic properties of laser beam is essential to understand students' background. This can be useful in preparing the course and improving student understanding. An assessment instrument consisting of 12 items was developed to investigate 606 freshmen students' knowledge in five basic properties of laser beam: directionality, beam divergence, intensity, speed, and monochromaticity. The reliability of the test was 0.5 measured by KR-20. The samples consisted of medical science students, science students, and agriculture and law students who participated in general physics courses. The average score from all students was 40%. The highest score was in the "directionality", while the lowest score was in the "speed of laser light". Additionally, the science students got the highest scores of 42%, which is still low. These results indicated that even though students were familiar with lasers, they still needed to improve their knowledge. © Common Ground, Jintawat Tanamatayarat, Kwan Arayathanitkul, Narumon Emarat, Ratchapak Chitaree.